Children’s Rights and the Sustainable Development Goals - Mensah, Cocou Marius (International Children's Rights, 2024)
This chapter explores the complex relationship between child rights and the United Nations Sustainable Development Goals (SDGs). Recognising the vital need to protect children’s well-being and ensure a sustainable future, this study critically examines the diverse legal dimensions, challenges, and opportunities that intersect as these two frameworks converge. By conducting a comprehensive analysis of the SDGs, international treaties, and various regional agreements, this chapter aims to shed light on the complex legal landscape and identify avenues for strengthening children’s rights in the context of sustainable development. The discussion encompasses various aspects, including quality education (SDG 4), gender equality (SDG 5), the right to a quality life (SDG 14), life on land (SDG 15), and global partnerships (SDG 17), examining how progress in these areas can have a profound impact on children’s rights. Furthermore, this chapter explores the role of states, international organisations, and civil society in promoting children’s rights within the framework of the SDGs. Overall, this chapter highlights the critical need to align SDGs with international child rights standards and offers recommendations to address gaps, strengthen legal protection, and ensure children’s active participation in pursuing a sustainable future.Keywords: children’s rights, sustainable development goals, global partnerships, child participation in sustainable development, youth empowerment